Stress distribution characteristics and crack propagation law of fractured hard rock influenced by opening degree - Baoxin Jia; Fengpu Liu (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Prefabricated fracture dip angles and openings are important factors affecting the damage pattern and breakage mechanism of fractured rock. In order to investigate the fracture mechanism of fractured hard rock under the interaction of different fracture openings and dip angles from mesoscopic view, indoor tests and numerical simulation tests of hard rock with specific fracture openings and multiple fracture dip angles have been carried out. The results show that the fracture openings and fracture dip angle together determine the mechanical properties of fractured hard rock. In particular, when β ≤ 45°, the effect of fracture openings on peak stress is significant, and when β > 45°, the effect of fracture openings on peak stress is small. When b ≤ 0.4 mm, the fracture opening degree has some effect on the crack initiation stress. When b > 0.4 mm, the effect of fracture opening degree on the crack initiation stress is small. The crack extension paths and damage modes of specimens with different fracture openings differed, and the differences were generally significant from the start of shear crack extension. The beam structure with different coupling characteristics at the end is used as a mechanical model to reflect the force characteristics of hard rock with different degrees of fracture opening, so as to reveal the damage mechanism of hard rock with different degrees of fracture opening. The damage characteristics of fractured hard rock under the interaction of different fracture openings and fracture dip angles are summarized, and it is found that fracture openings have a more significant effect on the damage characteristics of small-angle fractured hard rock. With the increase of fracture dip angle, the location of initiation cracks shifted from the middle of the fracture to the end of the fracture.